Kinetic Analysis of Lidocaine Elimination by Pig Liver Cells Cultured in 3D Multi-Compartment Hollow Fiber Membrane Network Perfusion Bioreactors - Gerardo Catapano; Juliane K. Unger; Elisabetta M. Zanetti; Gionata Fragomeni; Jörg C. Gerlach (Bioengineering, 2021)
Liver cells cultured in 3D bioreactors is an interesting option for temporary extracorporeal liver support in the treatment of acute liver failure and for animal models for preclinical drug screening. Bioreactor capacity to eliminate drugs is generally used for assessing cell metabolic competence in different bioreactors or to scale-up bioreactor design and performance for clinical or preclinical applications. However, drug adsorption and physical transport often disguise the intrinsic drug biotransformation kinetics and cell metabolic state. In this study, we characterized the intrinsic kinetics of lidocaine elimination and adsorption by porcine liver cells cultured in 3D four-compartment hollow fiber membrane network perfusion bioreactors. Models of lidocaine transport and biotransformation were used to extract intrinsic kinetic information from response to lidocaine bolus of bioreactor versus adhesion cultures. Different from 2D adhesion cultures, cells in the bioreactors are organized in liver-like aggregates. Adsorption on bioreactor constituents significantly affected lidocaine elimination and was effectively accounted for in kinetic analysis. Lidocaine elimination and cellular monoethylglicinexylidide biotransformation featured first-order kinetics with near-to-in vivo cell-specific capacity that was retained for times suitable for clinical assist and drug screening. Different from 2D cultures, cells in the 3D bioreactors challenged with lidocaine were exposed to close-to-physiological lidocaine and monoethylglicinexylidide concentration profiles. Kinetic analysis suggests bioreactor technology feasibility for preclinical drug screening and patient assist and that drug adsorption should be accounted for to assess cell state in different cultures and when laboratory bioreactor design and performance is scaled-up to clinical use or toxicological drug screening.